Use of spent coffee grounds as food ingredient in bakery products. (1st February 2017) - Martinez-Saez, Nuria; García, Alba Tamargo; Pérez, Inés Domínguez; Rebollo-Hernanz, Miguel; Mesías, Marta; Morales, Francisco J.; Martín-Cabrejas, María A.; del Castillo, Maria Dolores
Highlights: Spent coffee grounds are natural source of antioxidant dietary fibre. Coffee antioxidant dietary fibre is a food ingredient for use at high temperature. A food grade ingredient has been obtained from spent coffee grounds. Safety of spent coffee grounds can be easily controlled. Spent coffee grounds can be used in bakery products and other foodstuffs. Abstract: The present research aimed to evaluate the use of spent coffee grounds (SCG) from instant coffee as a food ingredient and its application in bakery products. Data on physicochemical characterization, thermal stability and food safety of SCG were acquired. Evaluation of feasibility as dietary fibre was also determined. Results showed SCG are natural source of antioxidant insoluble fibre, essential amino acids, low glycaemic sugars, resistant to thermal food processing and digestion process, and totally safe. In the present work, SCG were incorporated in biscuit formulations for the first time. Low-calorie sweeteners and oligofructose were also included in the food formulations. Nutritional quality, chemical (acrylamide, hydroxymethylfurfural and advanced glycation end products) and microbiological safety and sensory tests of the biscuits were carried out. Innovative biscuits were obtained according to consumers' preferences with high nutritional and sensorial quality and potential to reduce the risk of chronic diseases such as obesity and diabetes.